Pengembangan Materi Pembelajaran PAI Berbasis Toleransi - Farhan, Farhan; Widodo, Hendro (Yayasan Rahmat Islamiyah, 2023)
This study explains that the main idea of tolerance education lies in how everyone who comes from a different background can then be respected and accepted well so that a peaceful life can be realized in a plural and homogeneous society. To realize this, the authors put forward several principles that are used as the basis, namely: Pancasila as the basis of the state and the 1945 Constitution as well as strengthening the Koran which explains